2003
DOI: 10.1037/0735-7044.117.3.464
|View full text |Cite
|
Sign up to set email alerts
|

SEE locomotor behavior test discriminates C57BL/6J and DBA/2J mouse inbred strains across laboratories and protocol conditions.

Abstract: Conventional tests of behavioral phenotyping frequently have difficulties differentiating certain genotypes and replicating these differences across laboratories and protocol conditions. This study explores the hypothesis that automated tests can be designed to quantify ethologically relevant behavior patterns that more readily characterize heritable and replicable phenotypes. It used SEE (Strategy for the Exploration of Exploration) to phenotype the locomotor behavior of the C57BL/6 and DBA/2 mouse inbred str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 52 publications
2
67
0
1
Order By: Relevance
“…EthoVision was used to calculate the total distance traveled as well as the time spent and the number of entries into the center square area (20 × 20 cm). SEE (Software for the Exploration of Exploration; Kafkafi et al, 2003) was used to smooth path shape and calculate specific measures of locomotor behavior. SEE uses the distribution of speed peaks to parse the locomotor data slow local movements (so-called lingering episodes) and progression segments.…”
Section: Open Field Testmentioning
confidence: 99%
“…EthoVision was used to calculate the total distance traveled as well as the time spent and the number of entries into the center square area (20 × 20 cm). SEE (Software for the Exploration of Exploration; Kafkafi et al, 2003) was used to smooth path shape and calculate specific measures of locomotor behavior. SEE uses the distribution of speed peaks to parse the locomotor data slow local movements (so-called lingering episodes) and progression segments.…”
Section: Open Field Testmentioning
confidence: 99%
“…Open-field tests were conducted during the light phase of the cycle using the standard procedure in SEE (Software for the Exploration of Exploration; see Drai and Golani, 2001;Kafkafi et al, 2003a;. Briefly, each animal was injected once and immediately introduced to a 2.50 m diameter circular open-field arena for 60 min while its location was tracked using Noldus EthoVision video-tracking system at a rate of 30 Hz and the highest video resolution (480 Â 640 pixel).…”
Section: Drugs Animals and Experimental Proceduresmentioning
confidence: 99%
“…This approach, however, was not applied to locomotor patterns of arbitrary morphology and did not address pattern temporal structure, a fundamental limitation of simple Markov models. Algorithms that identify individual bouts of locomotor activity have also been reported (Drai et al 2000;Drai and Golani 2001;Golani et al 1999;Kafkafi et al 2003), but these techniques are not readily adaptable to the quantification of route-tracing stereotypies. Finally, in a novel use of ergodic theory, Paulus and colleagues demonstrated that both metric and topological entropy parameters could describe increased home-cage stereotypical locomotor behavior after psychostimulant treatment (Paulus et al 1990(Paulus et al , 1999Paulus and Geyer 1991).…”
Section: Introductionmentioning
confidence: 99%